2019
DOI: 10.1109/tsp.2019.2901356
|View full text |Cite
|
Sign up to set email alerts
|

Power Systems Topology and State Estimation by Graph Blind Source Separation

Abstract: In this paper, we consider the problem of blind estimation of states and topology (BEST) in power systems. We use the linearized DC model of real power measurements with unknown voltage phases (i.e. states) and an unknown admittance matrix (i.e. topology) and show that the BEST problem can be formulated as a blind source separation (BSS) problem with a weighted Laplacian mixing matrix. We develop the constrained maximum likelihood (ML) estimator of the Laplacian matrix for this graph BSS (GBSS) problem with Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 74 publications
(112 reference statements)
1
38
0
Order By: Relevance
“…The averaged threshold from (25) is statistically more robust to outliers than the maximum threshold from (24). Consistently, our simulations showed that, indeed, the threshold value from (25) led to better results than the one from (24).…”
Section: Detection Methodssupporting
confidence: 82%
“…The averaged threshold from (25) is statistically more robust to outliers than the maximum threshold from (24). Consistently, our simulations showed that, indeed, the threshold value from (25) led to better results than the one from (24).…”
Section: Detection Methodssupporting
confidence: 82%
“…It is because that graph signal recovery and estimate have been widely studied with many promising applications. Applications contain power systems estimation [55][56][57][58], network time synchronization, and data registration [59,60].…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%
“…In blind signal separation, the typical algorithms commonly used include the fast fixed-point algorithm [37], natural gradient algorithm [38], Equivariant Adaptive Separation via Independence (EASI) algorithm [39,40], and Joint Approximation Diagonalization of Eigen-matrices (JADE) algorithm [41,42], etc. Grotas et al [43] developed the constrained maximum likelihood (ML) estimator of the Laplacian matrix for this graph BSS problem with Gaussian-distributed states. Eitner et al [44] used two blind source separation algorithms to estimate the modal parameters of a reduced-scale rocket nozzle using only measurements of deformation.…”
Section: Introductionmentioning
confidence: 99%